DAMPAK KEBIJAKAN PROVISI SUMBERDAYA HUTAN DAN DANA REBOISASI TERHADAP KESEJAHTERAAN - Erwinsyah Erwinsyah; Harianto Harianto; Bonar M. Sinaga; Bintang C.H. Simangunsong (Jurnal Analisis Kebijakan Kehutanan, 2013)
In the last three decades the forestry sector has given important contributi on to the government revenues, among others are recieved from forest royalty (PSDH) and reforestation fund (DR). To determine the impact of implementation of PSDH and DR policy on welf are the nelasticity of supply and demand of roundwood market and wood products market were determined, and use from previous study. Data use din this study was time series from year 1995 to year 2009. This study was concluded that increasing PSDH and DR separately will increase the price of roundwood, except the price of pulp wood of HTI, and will increase the price of wood products. An increased DR and PSDH at the sametime will increase the price of roundwood and wood products. Increased PSDH will encourage higher production of roundwood and wood products, except of plywood which was not much influenced by increased market prices. Increased DR will increase roundwood production, except the pulp wood of HTI. Increased DR will increase production of sawn timber. While increased DR and PSDH will simultaneously increase the production of roundwood from natural forest, construction wood and pulp wood from HTI as well as sawn timber and pulp product. Increased PSDH and DR will increase producer welf are and reduce consumer welf are of round wood